2018
DOI: 10.1186/s12906-018-2199-4
|View full text |Cite
|
Sign up to set email alerts
|

Coconut water vinegar ameliorates recovery of acetaminophen induced liver damage in mice

Abstract: BackgroundCoconut water has been commonly consumed as a beverage for its multiple health benefits while vinegar has been used as common seasoning and a traditional Chinese medicine. The present study investigates the potential of coconut water vinegar in promoting recovery on acetaminophen induced liver damage.MethodsMice were injected with 250 mg/kg body weight acetaminophen for 7 days and were treated with distilled water (untreated), Silybin (positive control) and coconut water vinegar (0.08 mL/kg and 2 mL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…In response to the HLA diet, we not only observed decreased abundance of Akkermansia but also of Sutterella, and increased abundance of Butyricimonas and Coprococcus. Alterations in the abundances of these bacteria in response to increased dietary lipid intake have been reported previously (3,26,32), indicating that all of these genera may be sensitive to the fatty acid content of the diet. Human pregnancy has previously been reported to reduce the individual (alpha) diversity of the gut microbiota in humans (21) and rodents (15).…”
Section: Discussionsupporting
confidence: 64%
“…In response to the HLA diet, we not only observed decreased abundance of Akkermansia but also of Sutterella, and increased abundance of Butyricimonas and Coprococcus. Alterations in the abundances of these bacteria in response to increased dietary lipid intake have been reported previously (3,26,32), indicating that all of these genera may be sensitive to the fatty acid content of the diet. Human pregnancy has previously been reported to reduce the individual (alpha) diversity of the gut microbiota in humans (21) and rodents (15).…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, as was reported by Nishidai et al [29], vinegar produced by different types of acetic acid bacteria strains may have different levels of antioxidant activities. According to a study done by Mohamed et al [30], the total phenolic content of coconut water vinegar was found to be 106.45±0.01 µg GAE/ml, and the results obtained in the current study are also in accordance with the reported value. Moreover, as was reported by Bakir et al [31], vinegar produced from grapes and apples was found to have a total phenolic content of 220 mg GAE/L and 160 mg GAE/l, respectively.…”
Section: Examining the Bioactivity Of Produced Vinegarsupporting
confidence: 91%
“…Zulaikhah et al proved that the administration of 450 mL/day of TCW 30 days lowers MDA levels in traditional gold miners exposed to mercury 15 . Loki & Rajamohan reported that TCW was able to decrease MDA levels in CCl 4 -induced rats 13 . Agbafar et al, studies suggest that coconut water is capable of lowering MDA levels as lipid peroxidation markers 23 .…”
Section: Lipid Peroxidation Activity (Reduces Mda Levels)mentioning
confidence: 99%
“…TCW can be used as ready to drink food product having natural health beneficial nutrients 20 . 13 . The study of Zulaikhah et al, proved that the administration of TCW 450 mL/day for 30 days increased SOD and GPx levels in traditional gold miners exposed to mercury 15 .…”
Section: Health Benefits Of Tcw For Health: 1 Natural Isotonic Drmentioning
confidence: 99%
See 1 more Smart Citation